(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper talks about how bank credit was given to Micro, Small, and Medium Enterprises (MSMEs) in India. That was during the time from July 2021 to July 2022 [4]. MSMEs play a big role in India’s economy. But many of them, especially the small ones, have trouble in taking loans. This study used official data from the Reserve Bank of India (RBI). That data helped to show how credit was shared between different types of MSMEs. The graphs that were used were simple. These were made in R software. The results show one thing clearly. Credit to MSMEs has gone up during that one-year period. But the speed of increase was not the same for all. Medium enterprises got credit faster than Micro and Small ones. That means, even though the smaller firms are more in number, the medium ones are rising faster in bank support. This is a key point. The paper also gives some ideas. These are for how to improve credit access for smaller businesses. That is important because they still face many problems.